Formation of professional competence of the future specialist of profile international relations (on the example of the French language) (International relations and international law Journal, 2018)
Article is devoted to teaching and methodological issues in the teaching of foreign languages on the material of the French language which is taken as a basis for formation of professional competence of the future specialist of profile international relations. Under the competence of the future specialistrefers to the degree of mastery of general cultural and professional competences. General cultural competence determined by the willingness and ability of graduates to adapt to changes in the socio-political conditions, their organizational skills. Professional competence is characterized by the subject’s ability to master a certain amount of professional knowledge and ability to apply them in practice. Students must have basic terms of special, to be able to use special vocabulary when performing teaching professionally oriented tasks, be skilled in oral communication to communicate with colleagues – native speakers to be able to find and analyze information in a foreign language sources, read professional literature, as well as be skilled in business correspondence. It is expected that after completing the course of learning a foreign language, students should be able to compile the information and to issue it as an abstract, summary or report.Key words: formation, professional foreign language competence, adaptation, organizational skills, professional competence.